Prognostic value of tumor mutation burden in patients with advanced gastric cancer receiving first-line chemotherapy - Duan, Xiao-Peng; Liu, Ke; Jiao, Xiao-Dong; Qin, Bao-Dong; Li, Bing; He, Xi; Ling, Yan; Wu, Ying; Chen, Shi-Qi; Zang, Yuan-Sheng (Frontiers in Oncology, 2023)
Background: Tumor mutation burden (TMB) is a promising biomarker positively associated with benefit of immunotherapy and might predict outcome of chemotherapy. We described prognostic value of TMB in advanced gastric cancer and explored the underlying mechanism. Methods: We enrolled 155 TMB-evaluated advanced gastric cancer patients, and analyzed the relation between the clinicopathological information and both overall survival (OS) and progression-free survival (PFS) among forty of them treated with first-line chemotherapy. We further verified the distribution of TMB and analyzed the potential mechanism underlying the prognosis based on The Cancer Genome Atlas (TCGA) database. Results: Among the 155 patients, 29 (18.7%) were TMB-High (TMB≥10), roughly same as the proportion in TCGA data. Of the 40 patients receiving first-line chemotherapy, the median OS (7.9 vs. 12.1 months; HR 3.18; p=0.0056) and PFS (4.4 vs. 6.2 months; HR 2.94; p=0.0099) of tissue-tested TMB (tTMB)-High patients were inferior than that of tTMB-Low. Similarly, the unfavorable median OS (9.9 vs. 12.1 months; HR 2.11; p=0.028) and PFS (5.3 vs. 6.5 months; HR 2.49; p=0.0054) were shown in the blood-tested TMB (bTMB)-high compared with bTMB-Low. The cox analysis demonstrated that both tTMB-High and bTMB-High were significant independent predictors of dreadful OS and PFS. The differentially expressed genes (DEGs) according to TMB status were most significantly enriched in the downregulated metabolic pathway among TMB-High patients. Conclusions: TMB-High advanced gastric cancer patients accounted around 1/6 and had poorer prognosis than TMB-Low patients when treated with first-line chemotherapy. The potential mechanism might be the downregulated metabolic activity in TMB-High patients.